Natural fiber-reinforced high-density polyethylene composite hybridized with ultra-high molecular weight polyethylene. (June 2019) - Ning, Haibin; Pillay, Selvum; Lu, Na; Zainuddin, Shaik; Yan, Yongzhe
A great deal of research and development work has been recently conducted on natural fiber-reinforced polymer matrix composite for its abundancy, low density, excellent damping characteristic, and good mechanical properties. However, the low strength of natural fiber composite has limited its use to only low stress applications. The purpose of this work is to develop a natural fiber hybrid material with both enhanced strength and failure strain using a novel approach and study the effect of the processing temperature on its microstructure and performance. High-strength ultra-high molecular weight polyethylene fabrics are co-molded onto the surfaces of a kenaf fiber high-density polyethylene-based composite material by single-step compression molding. The status of the ultra-high molecular weight polyethylene fabrics at different processing temperatures is investigated using microscopic analysis. The tensile strength and impact strength of the hybrid material are evaluated. It is found that its tensile strength is increased by more than 90% with only 8% ultra-high molecular weight polyethylene fiber reinforcement added and its low density is maintained.